1999
DOI: 10.1136/bjo.83.4.478
|View full text |Cite
|
Sign up to set email alerts
|

Modulating phenotype and cytokine production of leucocytic retinal infiltrate in experimental autoimmune uveoretinitis following intranasal tolerance induction with retinal antigens

Abstract: Background/aim-Nasal administration of retinal antigens induces systemic tolerance which results in suppression of experimental autoimmune uveoretinitis (EAU) when subsequently exposed to antigen. The aim was to establish if tolerance induction alters retinal infiltrating leucocyte phenotype and cytokine profile in tolerised animals when there is significantly reduced tissue destruction despite immunisation with retinal antigen. Conclusions-Leucocytic infiltrate is not only reduced in number but its distinct p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Recent data in allergy, and autoimmune models including EAU, have shown that mucosal administration of autoantigen results in early activation followed by apoptosis of T cell populations and invoke a role for IL-10 in the generation of immunological non-responsiveness 1-316-19 Notably, in the EAU model, we demonstrated that although regulatory cells were generated, tolerance could only be transferred from spleen, and cells that did infiltrate the retina in treated animals produced IL-10 1920.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Recent data in allergy, and autoimmune models including EAU, have shown that mucosal administration of autoantigen results in early activation followed by apoptosis of T cell populations and invoke a role for IL-10 in the generation of immunological non-responsiveness 1-316-19 Notably, in the EAU model, we demonstrated that although regulatory cells were generated, tolerance could only be transferred from spleen, and cells that did infiltrate the retina in treated animals produced IL-10 1920.…”
mentioning
confidence: 70%
“…What is well appreciated is the involvement of cytokine activated STAT molecules in the regulation of T helper cell differentiation and apoptosis,38 and the ability of regulatory cytokines such as TGF-β to modulate this process 39. Despite previously demonstrating, after tolerance induction and immunisation, Th2 responses (IL-2 and IL-10 producing) from infiltrating T cells within retina,19 there remains little evidence to support a bias toward Th2 responses as a direct result of tolerance mechanisms within the lymph node 40. Here we have shown increased STAT4 signalling, concomitant with antigen specific proliferation, signifying Th1 reactivity and is in keeping with our previous data of a transient IFN-γ burst within SCLN17 and supports an initial T cell activating event.…”
Section: Discussionmentioning
confidence: 91%
“…Initial T cell priming and apoptosis have been described in regional drainage lymph nodes during oral tolerance [44][45][46]. We have recently shown that in tolerized animals, although structural damage is suppressed, a reduced CD4 + T cell infiltrate is still present and these cells produce IL-10 and IL-4 and reduced IFN- [47]. Possible mechanims by which activation-induced apoptosis is achieved are via both Fas-FasL [48] as well as non-Fas-mediated pathways [49], in which TGF-is a central component.…”
Section: Discussionmentioning
confidence: 98%
“…It is not clear what the signals are that support up-regulation of CD200R expression in MG during inflammation. Certainly a Th1 response in EAU with pronounced IFN-␥ and tumor necrosis factor-␣ activity 31,32 within the retina, may generate signals, which override the CD200:CD200R axis and activate cells. Given that the data strongly supports that in CD200 Ϫ/Ϫ mice MG are classically activated, we were surprised to observe that firstly; during peak disease, NOS2 expression was reduced compared to CD200 ϩ/ϩ mice and to that previously reported, 24,33,34 and secondly there was no significant increase, in photoreceptor destruction observed histologically.…”
Section: Discussionmentioning
confidence: 99%